The Role of Digital Content in Stimulating Visiting Decisions to Kampung Wisata Caping, Pontianak - Arweni, Arweni; Hendharsa, Angga; Rawa, Ricola Dewi; S, Yuana (Universitas Muhammadiyah Pontianak, 2026)
This study examines the role of firm-generated content (FGC) and user-generated content (UGC) in influencing tourist visiting decisions to Kampung Wisata Caping, Pontianak. Using a quantitative survey of 166 respondents and analyzed with structural equation modeling (SEM-PLS), the results reveal that UGC significantly affects both visit intention and decision, whereas FGC only influences visiting decisions directly, not intentions. Furthermore, visit intention mediates the relationship between UGC and visiting decisions but not between FGC and visiting decisions. These findings highlight the complementary roles of FGC as informational validation and UGC as a driver of authentic engagement in tourism marketing.